Graphene oxide nanoflakes from various agrowastes. Issue 3 (17th March 2020) - Naik, M.J.P.; Debbarma, J.; Saha, M.; Bhargava, A.
Abstract: Nowadays, the synthesis of graphene/ graphene oxide from graphite precursor using oxidizing agents is the most common procedure, but the direct synthesis of graphene or graphene oxide from a non‐graphitic carbonaceous material without using inert atmosphere is really a great challenge. Besides, the chemistry behind the development of graphitic structure from a non‐graphitic material during the thermal heating is still not clearly understood. In this research work, three agrowaste materials viz. rice husk, sugarcane bagasse and newspaper were selected and subjected to pyrolysis in presence of trace amount of air. The continued heating at the optimum temperature has resulted in aromatization and condensation along with the oxidation within the cellulosic structure of the agrowaste, which finally resulted in the formation of graphene oxide nanoflakes directly. The mechanism of formation of graphene oxide from these agrowaste materials was studied, which suggested that any carbonaceous waste materials can be converted to graphene oxide by optimizing the thermal heating conditions. Abstract : This method proved to be economic and energetically favorable to produce graphene oxide from non‐graphitic materials bypassing the use of graphite powders and other harsh chemicals. The process could lead to new opportunities for cost‐effective production of graphene derivatives and may be applied as potential materials for water purification, gas sensors, energy storage, etc.